2022
DOI: 10.21037/atm-22-5979
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immune- and autophagy-related genes and effective diagnostic biomarkers in endometriosis: a bioinformatics analysis

Abstract: Background: To identify autophagy-and immune-related hub genes affecting the diagnosis and treatment of endometriosis.Methods: Gene expression data were downloaded from the Gene Expression Omnibus (GEO) (GSE11691 and GSE120103 for training, and GSE7305 for validation). By overlapping the differentially expressed genes (DEGs), Weighted gene co-expression network analysis (WGCNA) module genes, and autophagyrelated genes (ARGs), and immune-related genes (IRGs) separately, hub genes were identified using the least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The chronic pain, reproductive challenges, and potential complications associated with it not only severely impact the physical health of patients but also their mental and emotional wellbeing, placing a heavy economic burden on society. We have identified a better diagnostic model than previously available ( Ji et al, 2022 ), and these data highlight the need for further research to uncover senescence-related mechanisms in EM. It has laid some foundation and direction for more in-depth research afterward.…”
Section: Discussionmentioning
confidence: 74%
“…The chronic pain, reproductive challenges, and potential complications associated with it not only severely impact the physical health of patients but also their mental and emotional wellbeing, placing a heavy economic burden on society. We have identified a better diagnostic model than previously available ( Ji et al, 2022 ), and these data highlight the need for further research to uncover senescence-related mechanisms in EM. It has laid some foundation and direction for more in-depth research afterward.…”
Section: Discussionmentioning
confidence: 74%
“…Their analyses, employing GO and KEGG, revealed that the identified similar genes were notably enriched in protein interactions, cellular barrier reinforcement, and cellular life dynamics (15). In a separate study, 22 endometriosis-related immune genes emerged from the overlap of 1 116 DEGs, featuring nine immune-related hub genes (BST2, CCL13, CD86, CSF1, FAM3C, GREM1, ISG20, PSMB8, S100A11) and nine ARG hub genes (GSK3A, HTR2B, RAB3GAP1, ARFIP2, BNIP3, CSF1, MAOA, PPP1R13L, SH3GLB2) (16). The heightened expression of these hub genes is intricately linked to diverse processes, including DNA methylation, protein thiol-disulfide exchange, chromatin silencing, myosin thick filament formation, and systemic development (17).…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of autophagy-related genes such as microtubule-associated protein light chain 3 (LC3) and Beclin-1 have been shown to be reduced in the serum, PF, and eutopic endometrial tissue of patients with EMs compared with the levels in healthy controls ( Sui et al, 2018 ), and the level of expression of autophagy-related genes (LC3B-II) was significantly reduced in ectopic endometrium compared with that in the eutopic endometrial tissues of patients with EMs ( Li et al, 2018 ). Inhibition of autophagy can promote the expression of inflammatory cytokines, trigger inflammation and immune responses leading to autoimmune damage, enable endometrial cells to evade immune surveillance, and ultimately promote ectopic growth and implantation of ectopic endometrial cells in the peritoneal cavity ( Ji et al, 2022 ). Autophagy and apoptosis are not two independent processes but two crosstalk mechanisms.…”
Section: Possible Associations Of Adiponectin With the Pathogenesis O...mentioning
confidence: 99%